Understanding the adverse impact of centralised care on neonatal outcomes - Shipley, Lara (2021)
Centralisation of neonatal intensive care has led to a reduction in mortality, but this has not translated into significant improvements in neurodisability. Understanding the factors contributing to adverse neurological outcomes in infants, especially those transported due to centralised care, could aid the reduction of long-term morbidity in these infants. Centralised care can also risk maternal-infant separation and result in a greater risk of additional stress on the parents of these infants. The aims of my thesis were to: 1) explore the current trends of in-utero transfer (IUT) and early postnatal transportation (PNT) in extremely preterm infants within the UK, 2) evaluate the relationship between early PNT of high-risk infants and severe intraventricular haemorrhage (IVH), 3) quantify the potential stressors for families of extremely preterm infants who undergo centralised care, 4) determine the UK prevalence and treatment of infants with hypoxic-ischaemic encephalopathy (HIE), and 5) explore the effects of whole body vibration (WBV), as experienced during neonatal transportation, on the developing brain.